Conceptual Approaches to the Education of Life-Meaningful Values of Teenagers and Early Adolescence in Ukraine - Zhurba Katherinа (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article presents the conceptual approaches to the upbringing in the education of lifemeaningful values of teenagers and early adolescence in Ukraine. The definition of life-meaningful values has been given up. The major problems and contradictions in the upbringing of the Ukrainian children were paid attention to. The dependence of the result of upbringing, from the desire and the participation of all actors: children, parents, teachers is pointed out. Conceptual approaches to education of life values meaning are analyzed on the methodological, theoretical and practical levels. The aspects of the previous researches have been underlined. In this context, a systematic approach determines the integrity of the educational process in primary and high school. Synergetic approach combines the organization and self-organization of the growing personality. Humanistic approach recognizes each child's highest value at school, family, and society. Personal-centered approach provides individual attention to him, to free choice of that or other life-meaningful values. Activity approach provides practice and deed activity of children and shows how the value of the meaning of life affects the behavior of the individual. The theoretical level of substantiation of the concept of education of children of teenagers and early youth gives ability to define key points and concepts. Practical level implies the corresponding experimental activity, the determination of propriate pedagogical conditions, the selection of content, forms and methods of education of teenagers and early adolescence. Conceptual approaches offer the opportunity to develop a modern system of education of the values of the meaning of life of teenagers and early adolescence in Ukraine. Implementation of conceptual approaches aimed at qualitative changes in the education of life-meaningful values among of teenagers and early adolescence